Speed Control of 3 Phase 1.5 kW Induction Motor using VSD LS SV015IG5A-2 with Proportional Integral Anti-Windup Method - Tahtawi, Adnan Rafi Al; Yahya, Sofian; Elbizzar, Passya; Ilman, Sofyan Muhammad (Peneliti Teknologi Teknik Indonesia, 2024)
The industrial world in Indonesia is experiencing increasing development. In general, most of the tools in the industrial world use electric motors as the main drive. Induction motors are alternate current (AC) electric motors that are most widely used to support performance in the industrial world. Factors that make induction motors widely used in the industrial world are due to high efficiency and performance, size that is not too large, easier maintenance, and does not cost much. The drawback of the induction motor itself is that controlling the speed of the induction motor is not easy and includes a non-linear motor. Therefore, the right technology is needed to regulate the speed of the induction motor to remain stable when given a change in load. The research conducted is the speed regulation of a 220 volt 1.5 kw 3 phase induction motor by adjusting the frequency using Variable Speed Drive LS SV015IG5A-2 with Arduino-based PI Anti-windup control. This control aims to get a constant 3-phase induction motor speed with a speed of 1200 Rpm when given a loading of 1-8 Nm with a maximum speed error value of ±6%, maximum rise time of 10s, maximum settling time of 10s. PI Anti-windup will reduce the integral calculation so that the PI value does not exceed the maximum limit and is less than the minimum limit of control saturation to maintain a better system response and responsiveness to changes in actual values triggered by varying load changes. Based on the test results of the induction motor speed regulation system using the PI Anti-windup method with a value of Kp = 4; Ki = 0.967; Ka = 0.884 which results in an average rise time of 2.12s, settling time of 4.882s, and steady state error of 0.606.